Is a government-regulated rehabilitation guideline more effective than general practitioner education or preferred-provider rehabilitation in promoting recovery from acute whiplash-associated disorders? A pragmatic randomised controlled trial. Issue 1 (24th January 2019) - Côté, Pierre; Boyle, Eleanor; Shearer, Heather M; Stupar, Maja; Jacobs, Craig; Cassidy, John David; Carette, Simon; van der Velde, Gabrielle; Wong, Jessica J; Hogg-Johnson, Sheilah; Ammendolia, Carlo; Hayden, Jill Alison; et al.
Abstract : Objective: To evaluate the effectiveness of a government-regulated rehabilitation guideline compared with education and activation by general practitioners, and to a preferred-provider insurance-based rehabilitation programme on self-reported global recovery from acute whiplash-associated disorders (WAD) grade I–II. Design: Pragmatic randomised clinical trial with blinded outcome assessment. Setting: Multidisciplinary rehabilitation clinics and general practitioners in Ontario, Canada. Participants: 340 participants with acute WAD grade I and II. Potential participants were sampled from a large automobile insurer when reporting a traffic injury. Interventions: Participants were randomised to receive one of three protocols: government-regulated rehabilitation guideline, education and activation by general practitioners or a preferred-provider insurance-based rehabilitation. Primary and secondary outcome measures: Our primary outcome was time to self-reported global recovery. Secondary outcomes included time on insurance benefits, neck pain intensity, whiplash-related disability, health-related quality of life and depressive symptomatology at 6 weeks and 3, 6, 9 and 12 months postinjury. Results: The median time to self-reported global recovery was 59 days (95% CI 55 to 68) for the government-regulated guideline group, 105 days (95% CI 61 to 126) for the preferred-provider group and 108 days (95% CI 93 to 206) for the general practitioner group; the difference was not statistically significant (Χ 2 =3.96; 2 df: p=0.138). We found no clinically important differences between groups in secondary outcomes. Post hoc analysis suggests that the general practitioner (hazard rate ratio (HRR)=0.51, 95% CI 0.34 to 0.77) and preferred-provider groups (HRR=0.67, 95% CI 0.46 to 0.96) had slower recovery than the government-regulated guideline group during the first 80 days postinjury. No major adverse events were reported. Conclusions: Time-to-recovery did not significantly differ across intervention groups. We found no differences between groups with regard to neck-specific outcomes, depression and health-related quality of life. Trial registration number: NCT00546806 .